(untitled) (Global Journal of Science Frontier Research, 2024)
Let me talk about three concepts first, which may not be very accurate but I haven’t found a better description. Radiation is the process by which particulate matter radiates energy as it cools. A quantum is a unit of energy radiated outward during the cooling process of particle matter. Temperature is a measure of the ability of particulate matter to radiate externally."The Law of Cooling", the matter composed of elementary particles, every atom in it, builds a temperature field that is high inside and low outside, continuously radiates energy outward, cools itself, and makes its own state more stable Stablize. At the same time, it is constantly absorbing the energy transmitted from other nearby atomic substances. Every substance composed of elementary particles maintains a balance in this dynamic state of heat release and heat absorption. Heat release is active and heat absorption is passive. There is a substantial difference between "The Law of Cooling" and "The Theorem of Heat Exchange" learned in middle school. Heat exchange is understood from the molecular level. The law of cooling is the heat exchange explained from the quantum level. It is important to note here that active cooling is a basic property of matter. This feature was previously unrecognized. What is the temperature? We use a thermometer to measure the temperature, high and low, what exactly are we measuring? In air, is the velocity of the gas being measured? Obviously not, is the amplitude of the crystal oscillator measured in the solid? Is pressure measured in liquids? Obviously neither.